Separation of bovine κ-casein glycomacropeptide from sweet whey protein products with undetectable level of phenylalanine by protein precipitation followed by anion exchange chromatography. Issue 1 (February 2018) - Nakano, Takuo; Ozimek, Lech; Betti, Mirko
Abstract : Bovine κ-casein glycomacropeptide (GMP) found in sweet whey is a 64 amino acid residue glycopeptide, which does not contain phenylalanine or other aromatic amino acids. There is, however, little information available concerning isolation of phenylalanine free GMP from sweet whey. In the study reported in this Research Communication, GMP was purified from three samples of sweet whey protein products (SWPP) by a procedure involving: (1) precipitation of protein by heat treatment; (2) precipitation of protein by pH shift to 4·6; and (3) diethylaminoethyl (DEAE)-Sephacel anion exchange chromatography of soluble portion of each sample obtained after removal of protein precipitates. The total protein precipitated with both heat treatment and pH shift accounted for average 61% of dry weight of SWPP. The GMP fraction obtained by DEAE-Sephacel chromatography accounted for average 7·5% of dry weight of SWPP. Amino acid analysis showed that there was no detectable level of phenylalanine in GMP fractions from all samples examined. The present method may help develop large scale methods of production of GMP.